2018
DOI: 10.3389/fpls.2018.01753
|View full text |Cite
|
Sign up to set email alerts
|

Terpene Synthase Genes in Quercus robur – Gene Characterization, Expression and Resulting Terpenes Due to Cockchafer Feeding

Abstract: Root herbivory caused by larvae of the forest cockchafer (Melolontha hippocastani) enhances the impact of drought on trees, particularly in oak forest rejuvenations. In Germany, geographically distant oak stands show differences in infestation strength by the forest cockchafer. While in Southwestern Germany this insect causes severe damage, oak forests in northern Germany are rarely infested. It is known that root-released volatile organic compounds (VOCs) are perceived by soil herbivores, thus guiding the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…We also report the partial sequences of the hypothetical FRS gene and its gene expression from G. heterophylla for the first time. We could only amplify an 800 bp fragment, but this fragment was long enough to identify as the hypothetical FRS gene based on the Blastn and phylogenic analyses [ 51 , 52 ]. Since the current information of the FRS gene is very limited (only nine FRS genes from four plant species were reported), we believe that our report can provide more diversity in FRS sequences.…”
Section: Discussionmentioning
confidence: 99%
“…We also report the partial sequences of the hypothetical FRS gene and its gene expression from G. heterophylla for the first time. We could only amplify an 800 bp fragment, but this fragment was long enough to identify as the hypothetical FRS gene based on the Blastn and phylogenic analyses [ 51 , 52 ]. Since the current information of the FRS gene is very limited (only nine FRS genes from four plant species were reported), we believe that our report can provide more diversity in FRS sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Terpene synthases, key enzymes in terpenoids biosynthesis, then catalyse rearrangements and cyclisation producing a wide variety of monoterpene end-products (Black et al, 2015). Oak Quercus species are one of the strongest emitters of monoterpenoids (Loreto et al, 2002), and several terpene synthase genes coding for these enzymes have been identified (Creyaufmüller et al, 2018;Loreto et al, 2009). Despite this they do not contribute to aroma directly.…”
Section: Identification Of New Terpenoid Derivatives In Whisky and Oa...mentioning
confidence: 99%